2022
DOI: 10.3390/rs14163849
|View full text |Cite
|
Sign up to set email alerts
|

Trend in Satellite-Observed Vegetation Cover and Its Drivers in the Gannan Plateau, Upper Reaches of the Yellow River, from 2000 to 2020

Abstract: The Yellow River basin (YRB) has played an important role in the forming of Chinese civilization. Located in the upper reaches of the YRB and the southeastern edge of the Qinghai–Tibet Plateau (QTP), the Gannan Plateau (GP), which consists of mainly alpine and mountain ecosystems, is one of the most important water conservation areas for the Yellow River and recharges 6.59 billion cubic meters of water to the Yellow River each year, accounting for 11.4% of the total runoff of the Yellow River. In the past 30 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In this study, we employed the trend analysis method to evaluate the trend of fraction of vegetation cover (FVC) values over an extended time series. The trend analysis method utilizes the least squares method to compute the slope for each image element, thereby elucidating the long-term trend of vegetation cover [34,35]. The slope calculation formula is provided below:…”
Section: Trend Analysis and Significance Testmentioning
confidence: 99%
“…In this study, we employed the trend analysis method to evaluate the trend of fraction of vegetation cover (FVC) values over an extended time series. The trend analysis method utilizes the least squares method to compute the slope for each image element, thereby elucidating the long-term trend of vegetation cover [34,35]. The slope calculation formula is provided below:…”
Section: Trend Analysis and Significance Testmentioning
confidence: 99%
“…Our findings are consistent with Liu et al's research [50], which showed denser corridors in the northeast and southwest regions (Figure 7a). In the upper reaches, harsh environmental conditions limit the formation of large-scale forests, causing forest sources to be scattered and corridors to be long [51,52]. Therefore, the sources in the upper reaches rely heavily on the connecting role of corridors.…”
Section: Applications Of Forest Ecospatial Network In the Yellow Rive...mentioning
confidence: 99%
“…Second, three papers address spatiotemporal changes in snow cover and vegetation [11][12][13]. Zhao et al [11] used the daily MODIS cloud-free snow cover product to calculate various snow phenology variables, including snow cover area (SCA), snow cover onset (SCS), snow cover melt (SCM) and snow cover day (SCD).…”
Section: Overview Of Contribution and Future Perspectivesmentioning
confidence: 99%